Water sorption of heat-cured acrylic resin - Ammar Kh Al-Nori; Ahmed MA Hussain; Lamia T Rejab (University of Mosul, College of Dentistry, 2007)
Aims: To evaluate the effect of the different curing methods conventional water bath heat-curing and microwave energy curing method and different immersion periods on the water sorption and solubility of the different types of heat-cured acrylic resins. Materials and methods: Water sorption and solubility were measured by means of mass change in the materials after water saturation and dehydration. Two different commercial heat-cured acrylic resins Major Base 2, and Quayle Dental resins were used in this study. Specimens were divided into two groups depending on the curing method. Thirty two specimens were prepared, eight specimens for each material in each group. Specimens were immersed in distilled water, and then subsequently removed from their containers at 1 week and 1 month of immersion for evaluation. Mean values wear compared statistically with one way analysis of variance followed by Duncan's multiple range test to determined the significant different among the groups at (p< 0.05) level of significance. Results: showed that the curing method and immersion period have a significant effect on the water sorption and solubility ratios of the resins. Curing by microwave energy method and increasing immersion period caused increasing in the ratios. The type of heat-cured acrylic resin has an effect but the difference was not significant. Conclusion: the curing method, immersion period and types of the acrylic resin have an effect on the absorption and solubility ratios.